MICS/ISM Meander-Line Microstrip Antenna Encapsulated in Oblong-Shaped Pod for Gastrointestinal Tract Diagnosis - Supakit Kawdungta; Akkarat Boonpoonga; Chuwong Phongcharoenpanich (Sensors, 2021)
| ≤ -10 dB) for the MICS and ISM bands were 398-407 MHz and 2.41-2.48 GHz. The measured antenna gains were -38 dBi and -13 dBi, with a quasi-omnidirectional radiation pattern. The measured SAR was substantially below the maximum safety limits. As a result, the described MICS/ISM microstrip antenna encapsulated in an oblong-shaped pod can be used for real-time gastrointestinal tract diagnosis. The novelty of this work lies in the use of a meander-line microstrip, flipped-L defected ground plane, and loading resistor to miniaturize the antenna and realize the MICS and ISM bands.
Keywords: Wireless Body Area Networks; Antenna Design and Analysis; Wireless Power Transfer Systems